Gene Silencing and Over-Expression Studies in Concurrence With Promoter Specific Elicitations Reveal the Central Role of WsCYP85A69 in Biosynthesis of Triterpenoids in Withania somnifera (L.) Dunal - Sharma, Arti; Rather, Gulzar A.; Misra, Prashant; Dhar, Manoj K.; Lattoo, Surrinder K. (Frontiers in Plant Science, 2019)
Withania somnifera (Ashwagandha) synthesises a wide spectrum of triterpenoids that are produced via an intricate isoprenoid pathway whose biosynthetic and regulatory mechanism is yet elusive. Their pharmacological examinations position them as potent bioactive molecules hence demanding their copious production. Previous investigations reveal that P450s monooxygenases are pivotal enzymes involved in biosynthetic machinery of various metabolites and assist in decorating their core skeletal structures. Present study entails the isolation and functional characterization of castasterone synthase (CYP85A69) from W. somnifera. The full length WsCYP85A69 having an open reading frame of 1413 bp encodes 470 amino acid residues. Further, in vitro conversion of 6-deoxocastasterone into castasterone validated its oxidative functionality. Product formation was confirmed using LC-PDA-MS with m/z value of 506 [M+ACN]+. In planta transient over-expression of WsCYP85A69 significantly enhanced castasterone, stigmasterol and withanolides (WS-I, WS-II, WS-III). Artificial micro-RNA mediated silencing of WsCYP85A69 resulted in reduced accumulation of castasterone, stigmasterol and withanolides (WS-I, WS-II, WS-III). Taken together, these non-complementary approaches plausibly suggest a key role of WsCYP85A69 in the biosynthesis of castasterone and accumulation of withanolides and stigmasterol. Furthermore, promoter analysis of WsCYP85A69 resulted in the identification of several potential cis-regulatory elements. Elicitations given on the basis of identified cis-regulatory elements demonstrated methyl jasmonate as an effective inducer of WsCYP85A69. Overall, these empirical findings suggest that functional characterization of WsCYP85A69 may conceivably be helpful to unravel the mechanism of brassinosteroids biosynthesis and could also pave way for targeted metabolic engineering.